Combination chemotherapy with taxane and platinum in patients with salivary gland carcinoma: a retrospective study of docetaxel plus cisplatin and paclitaxel plus carboplatin - Onaga, Ryutaro; Enokida, Tomohiro; Ito, Kazue; Ueda, Yuri; Okano, Susumu; Fujisawa, Takao; Wada, Akihisa; Sato, Masanobu; Tanaka, Hideki; Takeshita, Naohiro; Tanaka, Nobukazu; Hoshi, Yuta; et al. (Frontiers in Oncology, 2023)
Background: Despite advances in precision medicine, most patients with recurrent or metastatic salivary gland carcinoma still need conventional chemotherapies, such as the combination of taxane and platinum. However, evidence for these standardized regimens is limited. Methods: We retrospectively reviewed patients with salivary gland carcinoma treated with a taxane and platinum, which contained docetaxel at a dose of 60 mg/m2 plus cisplatin at a dose of 70 mg/m2 on day 1, or paclitaxel at a dose of 100 mg/m2 plus carboplatin at a dose of area under the plasma concentration-time curve = 2.5 on days 1 and 8 (both on 21-day cycles), between January 2000 and September 2021. Results: Forty patients with ten adenoid cystic carcinomas and thirty other pathologies were identified. Of these, 29 patients were treated with docetaxel plus cisplatin and 11 with paclitaxel plus carboplatin. For the total population, the objective response rate (ORR) and median progression-free survival (mPFS) were 37.5% and 5.4 months (95% confidence interval: 3.6–7.4 months), respectively. On subgroup analysis, docetaxel plus cisplatin provided favorable efficacy compared with paclitaxel plus carboplatin (ORR: 46.5% vs. 20.0%, mPFS: 7.2 vs. 2.8 months), and the findings were well retained in patients with adenoid cystic carcinoma (ORR: 60.0% vs. 0%, mPFS: 17.7 vs. 2.8 months). Grade 3/4 neutropenia was relatively frequent in the docetaxel plus cisplatin (59% vs.27%), although febrile neutropenia was uncommon (3%) in the cohort. No treatment-related death was seen in any case. Conclusion: The combination of taxane and platinum is generally effective and well-tolerated for recurrent or metastatic salivary gland carcinoma. In contrast, paclitaxel plus carboplatin appears unfavorable in terms of efficacy in certain patients, such as those with adenoid cystic carcinoma.